Connecting growth with gene expression: of noise and numbers. (June 2015) - Shahrezaei, Vahid; Marguerat, Samuel
Highlights: Cellular growth, gene expression, and cell size are coordinated globally. Cellular growth is connected to protein numbers, noise, and gene networks dynamics. Global feedback through growth is an emerging layer of gene regulation. Coarse-grained models of cell physiology are essential to capture global feedback. Abstract : Growth is a dynamic process whereby cells accumulate mass. Growth rates of single cells are connected to RNA and protein synthesis rates, and therefore with biomolecule numbers. Noise in gene expression depends on these numbers, and is thus linked with cellular growth. Whether these global attributes of the cell participate in gene regulation is still largely unexplored. New experimental and modelling studies suggest that systemic variations in biomolecule numbers can coordinate cellular processes, including growth itself, through global regulatory feedback that acts in addition to genetic regulatory networks. Here, we review these findings and speculate on possible implications of this less appreciated layer of gene regulation for cellular physiology and adaptation to changing environments.